Philippine Literature and Communication Arts - Payawal-Gabriel Josefina (Quezon City : St. Bernadette Publishing House Corporation, 2014)
Philippine Literature and Communication Arts, your textbook in English, is in consonance with the overall goal of the new curriculum. The main objective of the book is to develop your communicative competence, and literary competence appreciation. communicative competence in English means the ability to use the English language in real-life situations like participating in class discussions or listening to a lecture. This type of competence includes the knowledge of grammar, social conventions related to language use, coherence in talking and writing, and the use of nonverbal cues. On the other hand, literary competence appreciation is the ability to perceive and comprehend direct and implied meaning of texts, and to respond to what is read by critical thinking, problem solving, decision making, and transferring knowledge to new situations."
Includes index glossary acknowledgment
English text